The development and new perspectives of stroke treatment in Poland - Kaczorowski, Rafał; Murjas, Barbara; Bartosik-Psujek, Halina (European Journal of Clinical and Experimental Medicine, 2015)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Stroke is one of the few neurological disorders known since antiquity. It is a clinical syndrome characterized by a sudden focal, and sometimes generalized brain dysfunction whose symptoms persist for more than 24 hours or sooner leads to death and has no other reason than vascular. This disease is common, approximately 15 million people fall ill with a stroke a year. In developed countries it is the third most common cause of adult disability and the second cause of dementia syndromes. The article presents the history of treatment of a stroke in Poland from the first mention in the textbooks on neurology from the 50’s to the present time. The past two decades proved to be the breakthrough in the treatment of strokes, when a significant change in the approach to this disease was adopted. Stroke from a hopeless state has become an acute illness, on the treatment of which neurologists have an increasing impact. Initially, the treatment of a stroke involved only patient care and prevention of systemic complications and bedsores. It was not until the 2nd half of the 90’s of the twentieth century that specialized stroke units were established, providing comprehensive care for patients. A breakthrough was an introduction of the rt-PA -recombinant tissue plasminogen activator to the treatment whose task is recanalization of a vessel closed by a blood clot or embolism in the acute period of the disease. This treatment significantly improved the functional status of patients. For the last several years, the concept of mechanical recanalization of the intracranial vascular system has developed, whose first tests have been conducted in several centers in Poland.